Study protocol of translation into Spanish and cross‐cultural adaptation and validation of the problem areas in diabetes-Pediatric version (PAID‐Peds) survey - Josep‐Oriol Casanovas‐Marsal; Elisa Civitani Monzón; María Pilar Ferrer Duce; Delia González de la Cuesta; Rosa Yelmo Valverde; Victoria Pérez Repiso; Irune Goicoechea Manterola; Antonio de Arriba Muñoz (Wiley, 2024)
Abstract Aim The metabolic and psychological management of paediatric type 1 diabetes mellitus (T1DM) can be challenging over time given that T1DM may cause a negative emotional burden and, consequently, result in poor metabolic control of the disease. The objectives of this study are to translate the Problem Area in Diabetes Survey-Pediatric version (PAID‐Peds) into Spanish, adapt it culturally and validate it. Design Multicenter cross sectional study. Methods 636 patients aged 8-17 years, diagnosed with T1DM, under treatment with insulin and follow‐up at the Miguel Servet University Hospital in Zaragoza (Aragón, Spain), the Ramón y Cajal University Clinical Hospital in Madrid (Spain) and at the Sant Joan de Déu Hospital in Barcelona (Catalonia, Spain) between 1 January 2023 and 31 December 2024 will be included. This study will consist of two phases: (1) Translation and cultural adaptation of the original PAID‐Peds® survey into Spanish following eight steps; (2) Validation of the Spanish version of the PAIS‐Peds® survey. The statistical analysis will be performed using Jamovi® 2.1.23. The reliability or internal consistency will be calculated using Cronbach's alpha index (considering an index higher than 0.8 to be good) and the test-retest will be evaluated using the intraclass correlation coefficient. For validity, confirmatory factor analysis will be calculated. This study has been approved by the ethics and research committees at each centre. Results The translation and validation into Spanish language of the Problem Area in Diabetes Survey‐Pediatric version will be feasible, valid and reliable to detecting the youth‐perceived burden of T1DM. Therapeutic education in diabetes-recommended by the WHO and the Diabetes Education Study Group-has shown encouraging results in glycaemia and psychosocial and behavioural factors in T1DM.